An Approach to Developing Local Climate Change Environmental Public Health Indicators in a Rural District. (2nd March 2017) - Houghton, Adele; Austin, Jessica; Beerman, Abby; Horton, Clayton
Abstract : Climate change represents a significant and growing threat to population health. Rural areas face unique challenges, such as high rates of vulnerable populations; economic uncertainty due to their reliance on industries that are vulnerable to climate change; less resilient infrastructure; and lower levels of access to community and emergency services than urban areas. This article fills a gap in public health practice by developing climate and health environmental public health indicators for a local public health department in a rural area. We adapted the National Environmental Public Health Tracking Network's framework for climate and health indicators to a seven-county health department in Western Kentucky. Using a three-step review process, we identified primary climate-related environmental public health hazards for the region (extreme heat, drought, and flooding) and a suite of related exposure, health outcome, population vulnerability, and environmental vulnerability indicators. Indicators that performed more poorly at the county level than at the state and national level were defined as "high vulnerability." Six to eight high vulnerability indicators were identified for each county. The local health department plans to use the results to enhance three key areas of existing services: epidemiology, public health preparedness, and community health assessment.